Superiority of 18F-FNa PET/CT for Detecting Bone Metastases in Comparison with Other Diagnostic Imaging Modalities - Lapa, Paula (2017)
Introduction: The 18F-NaF positron emission tomography/computed tomography is being considered as an excellent imaging modalityfor bone metastases detection. This ability was compared with other imaging techniques.Material and Methods: We retrospectively evaluated 114 patients who underwent 18F-NaF positron emission tomography/ computed tomography. Of these, 49 patients also had bone scintigraphy, 61 18F-FDG positron emission tomography/computed tomography and 10 18F-FCH positron emission tomography/computed tomography. We identified the technique that detected the largest number of bone metastases. For the detection of skeletal metastases with the 18F-NaF positron emission tomography/computed tomography study,the contribution of the positron emission tomography component was compared with the contribution of the computed tomography component. Cases in which 18F-NaF positron emission tomography/computed tomography and bone scintigraphy required further additional tests for diagnosis clarification were registered.Results: The 18F-NaF positron emission tomography/computed tomography was superior to bone scintigraphy in 49% of the patients(p < 0.001); it was superior to 18F-FDG positron emission tomography/computed tomography in 59% of the patients (p < 0.001) and it was superior to 18F-FCH positron emission tomography/computed tomography in 40% of the patients (p < 0.001). None of the compared imaging techniques were superior to 18F-NaF positron emission tomography/computed tomography. The positron emission tomography component was superior to computed tomography in 35% of the cases (p < 0.001). Further investigation was suggested in only 3.5% of patients who underwent 18F-NaF positron emission tomography/computed tomography (45% for bone scintigraphy) (p < 0.001).Discussion: As with other authors, our experience also confirms that 18F-NaF positron emission tomography/computed tomography is an excellent imaging modality for the detection of bone metastases, detecting lesions in more patients and more lesions per patient.Conclusion: The 18F-NaF positron emission tomography/computed tomography showed a superior ability for the detection of bone metastases when compared with bone scintigraphy, 18F-FDG positron emission tomography/computed tomography and 18F-FCH positron emission tomography/computed tomography.